Tuberculosis risk factors in children with smear-positive tuberculosis adult as household contact - Nora Hajarsjah; Ridwan M. Daulay; Oke Rina Ramayani; Wisman Dalimunthe; Rini Savitri Daulay; Fathia Meirina (Paediatrica Indonesiana, 2018)
Background Children in household contact of adults with smear-positive tuberculosis (TB) are at higher risk of TB infection. Screening of these children is a main strategy for eliminating childhood TB.Objective To determine risk factors of TB among children in household contact with smear-positive adult TB patients.Methods This case-control study was conducted in 5 public health centers at Batu Bara District, North Sumatera. We studied children from birth to 18 year-old living in the same house as adults with smear-positive TB. A tuberculosis scoring system was used to diagnosis TB in the children. Associations between risk factors and the incidence of TB were analyzed using Chi-square, Mann-Whitney U, and logistic regression tests.Results We enrolled 145 children who had household contact with smear-positive adult TB patients. Subjects were allocated to either the case group [TB score >6; 61 subjects (42.0%)] or the control group [TB score <6; 84 subjects (58.0%)]. Bivariate analysis revealed that nutritional status, immunization status, number of people in the house, sleeping in the same bed, and duration of household contact had significant associations with the incidence of TB. By multivariate logistic regression analysis, nutritional status and duration of household contact were significant risk factors for TB, with OR 5.89 and 8.91, respectively.Conclusion Malnutrition and duration of household contact with smear-positive adult TB patients of more than 6 hours per day were risk factors for TB among children.